Numerical investigation on flame propagation and pressure development in vented explosion - Mohd. Zaidi, Nur Hazwani Fatihah (2017)
The understanding of the explosion phenomenon is essential for an effective and safe engineering practice, particularly in refinery and chemical plants. Explosion venting technology is one of the effective techniques in protection measures against accidental internal gas explosions by relieving the pressure generated within the volume. The factors governing to the explosion development such as geometry, ignition position and vent burst pressure have been extensively studied. However, the details physical and dynamic mechanism responsible for the generation of significant pressure peaks during vented explosions is insufficient, making it difficult for designing the accurate explosion reliefs in practical situations. The primary motivation of this research was to better understand the turbulent flame propagation in vented gas explosion using modelling approach. Computational Fluid Dynamic (CFD) analyses using ANSYS Fluent is adopted to study the vented gas explosions process. Computations of the deflagrating flames were run in small-scale combustion chambers with two different volume sizes of 0.02 m3 and 0.0065 m3, closed at the one end and open at the opposite face. Only stoichiometric concentration of hydrogen, propane and methane-air mixtures were considered with different ignition positions (end and central ignition) and vent static burst pressure (Pv). The condition of the analysis was following experimental data done from previous researcher. From the findings, end ignition gave higher reduced overpressure on simulation results, about 1.4 times higher compared to central ignition due to the larger flame surface area attained. Thus, the time flame needed to reach the venting area became longer. The vents inclusion in the enclosures caused the reduction on the peak overpressure. As the Pv was further increased, i.e. from 98 mbar to 424 mbar, the venting effectiveness became lesser by 24 % for the methane explosion but not to the vented propane explosion in simulation analysis. This work confirmed that fuel reactivity gave important role on determining the venting effectiveness as stoichiometric hydrogen attained higher reduced explosion pressure (Pred) of 4.150 bar compared that of stoichiometric methane and propane vented explosion, 0.945 and 1.045 bar, respectively, if ignited at central location. It can be said that the distance from the location of ignition to the vent area, the fuel reactivity and Pv have significant roles to determine the duration of the pressure build up and the amount of vented mass, which describes the external explosion intensity.